2023
DOI: 10.1088/2058-6272/ac8e45
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of cusp stabilization in Keda Mirror with AXisymmetricity (KMAX)

Abstract: Stabilization of the axisymmetric magnetic mirror relies on the pressure-weighted magnetic field curvature. We report a new experiment by configuring a magnetic cusp structure to stabilize m = 1 interchange mode in KMAX tandem mirror. The cusp configuration is formed by reversing currents in the two side cell coils, and a stronger cusp can lead to a more stable plasma once the null point of cusp is less than 35–40 cm away from the device axis. The density fluctuations measured by four axial Langmuir probes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is interesting and to some extent unexpected that such a plate, contrary to well-founded fears, did not lead to degradation of plasma parameters, even if it was placed relatively close to the neck of the magnetic plug. Variant z E > 1 simulates a terminal MHD stabilizer of the cusp type [38][39][40][41][42][43].…”
Section: Mhd Stabilization By End Anchorsmentioning
confidence: 99%
“…It is interesting and to some extent unexpected that such a plate, contrary to well-founded fears, did not lead to degradation of plasma parameters, even if it was placed relatively close to the neck of the magnetic plug. Variant z E > 1 simulates a terminal MHD stabilizer of the cusp type [38][39][40][41][42][43].…”
Section: Mhd Stabilization By End Anchorsmentioning
confidence: 99%
“…Second, plasma stabilization will be required to enhance plasma performance. Previous studies showed that it was essential to suppress the MHD instabilities for better confinement (England et al 2009;Ryutov et al 2011;Qing et al 2023). In the near future, we will scan the location of the collector to adjust the stability of the interchange mode.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…2011; Qing et al. 2023). In the near future, we will scan the location of the collector to adjust the stability of the interchange mode.…”
Section: Summary and Future Workmentioning
confidence: 99%